Sustainable materials in ecological buildings - Piotr Czopka (Economic and Environmental Studies (E&ES), 2018)
Circular economy (CE) is a new trend in balanced development, directed at limiting consumption of resources and minimising waste production. In consideration of the European Commission's (EC) postulates of the CE implementation, the article aims at verifying whether coal power plants in Ma±opolska Province are aware of the CE notion, ready to think and act in compliance with its rules, and to show how their present activities align with this new trend. The results of the study present the energy sector in the context of transformation from linear economy to circular economy and formation of the bases for further development as well as for intensification of activities related to the implementation of the CE.
Keywords: Q01; Q20; 330; sustainable development; building materials; ecological building; product life-cycle